2021
DOI: 10.3389/fendo.2021.675581
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA 4977 bp Deletion in Peripheral Blood Is Associated With Polycystic Ovary Syndrome

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is a common endocrine disorder worldwide. We aimed to examine the associations of two mitochondrial DNA (mtDNA) biomarkers in the peripheral blood, mtDNA copy number (CN), and mtDNA4977 deletion rate (DR), with PCOS in a clinical setting.MethodsWe performed a study involving 263 women with PCOS and 326 age-matched controls between June 2015 and June 2019. The mtDNA CN and mtDNA4977 DR were measured using multiplex probe-based qPCR. The associations of the mtDNA CN and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Studies reporting the mtDNA copy number in the peripheral blood of PCOS patients compared to controls had mixed results. Only one study reported a higher mtDNA copy number [91], whereas multiple studies, including a robust meta-analysis, reported a significantly lower mtDNA copy number [49,[92][93][94]. The former study used a multiplex assay that paired the mtDNA copy number with the common mtDNA 4977 bp (mtDNA 4977 ) deletion, and the copy number was calculated using a minor arc segment [91].…”
Section: Peripheral Markers Of Mitochondrial Dysfunction In Pcosmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reporting the mtDNA copy number in the peripheral blood of PCOS patients compared to controls had mixed results. Only one study reported a higher mtDNA copy number [91], whereas multiple studies, including a robust meta-analysis, reported a significantly lower mtDNA copy number [49,[92][93][94]. The former study used a multiplex assay that paired the mtDNA copy number with the common mtDNA 4977 bp (mtDNA 4977 ) deletion, and the copy number was calculated using a minor arc segment [91].…”
Section: Peripheral Markers Of Mitochondrial Dysfunction In Pcosmentioning
confidence: 99%
“…Only one study reported a higher mtDNA copy number [91], whereas multiple studies, including a robust meta-analysis, reported a significantly lower mtDNA copy number [49,[92][93][94]. The former study used a multiplex assay that paired the mtDNA copy number with the common mtDNA 4977 bp (mtDNA 4977 ) deletion, and the copy number was calculated using a minor arc segment [91]. The investigators also adjusted findings for BMI and hormone levels, which negated the significance [91].…”
Section: Peripheral Markers Of Mitochondrial Dysfunction In Pcosmentioning
confidence: 99%
“…The 4977-bp deletion is one of the most common deletions of mtDNA, spanning approximately a third of the entire mitochondrial genome (nucleotides 8470–13,447), and is regarded as a pathogenic deletion in PCOS. 62 , 63 The 4977-bp deletion removes five tRNAs and seven genes encoding respiratory chain complexes that are important for normal OxPhos functions. The 4977-bp deletion results in an impairment of protein synthesis and reduces ATP and mtDNA copy number.…”
Section: -Bp Deletionmentioning
confidence: 99%
“…These factors strongly determine oocyte quality by in uencing zygote activation by triggering a Ca2 + + wave, affecting fertility [24,42]. Mutations in mtDNA also have been implicated in mitochondrial dysfunction, associated with polycystic ovary syndrome in humans [35,[43][44][45]. and lead to reduced mitochondrial functions.…”
Section: Associated Polymorphism a > G Transition At Position 869 Of ...mentioning
confidence: 99%